ANÁLISE DE REMANESCENTES FLORESTAIS NO MUNICÍPIO DE JABOTICABAL, SP - Facincani Dourado, Gustavo; de Oliveira Costa, Beatriz; Henrique Zeviani, Caio; Cristina Tarlé Pissarra, Teresa (Electronic Journal "Fórum Ambiental da Alta Paulista", 2013)
.